Template synthesis of mesoporous Li2MnSiO4@C composite with improved lithium storage properties. (20th November 2018) - Qiu, Shen; Pu, Xiangjun; Ai, Xinping; Yang, Hanxi; Chen, Zhongxue; Cao, Yuliang
Abstract: Li2 MnSiO4 is considered as a promising cathode candidate for high energy density Lithium-ion batteries (LIBs), due to its high theoretical capacity, favorable working potential as well as the low-cost and non-toxic nature of manganese element. However, it suffers from low capacity utilization and inferior cycling performance, due to the structural rearrangement upon cycling, phase impurities and manganese dissolution. To address these issues, nanostructure construction and carbon coating proves to be effective approach. In this work, we introduce an in situ template synthesis of a phase-pure Li2 MnSiO4 @C (MP-LMS@C) composite, which exhibits unique mesoporous morphology with nanosized Li2 MnSiO4 granules homogenously encapsulated in the interconnected carbon networks. Such unique Li2 MnSiO4 @C structure not only facilitates electron conduction and Li + transport, but also suppresses the manganese dissolution, as a result, the mesoporous Li2 MnSiO4 @C cathode exhibits greatly improved electrochemical performance, with a high specific capacity of 230 mAh g −1, good rate capability and superior capacity retention of 81% over 100 cycles.